2007
DOI: 10.1016/j.micpath.2007.05.007
|View full text |Cite
|
Sign up to set email alerts
|

γ-Glutamyl transpeptidase has a role in the persistent colonization of the avian gut by Campylobacter jejuni

Abstract: The contribution of gamma-glutamyl transpeptidase (GGT) to Campylobacter jejuni virulence and colonization of the avian gut has been investigated. The presence of the ggt gene in C. jejuni strains directly correlated with the expression of GGT activity as measured by cleavage and transfer of the gamma-glutamyl moiety. Inactivation of the monocistronic ggt gene in C. jejuni strain 81116 resulted in isogenic mutants with undetectable GGT activity; nevertheless, these mutants grew normally in vitro. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
80
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 57 publications
8
80
0
1
Order By: Relevance
“…A number of recent studies have also demonstrated the importance of C. jejuni factors modulating metabolism and physiology during the colonization of animal hosts. These include nutrient utilization systems such as the cj0480c-cj0490 operon, allowing C. jejuni to use L-fucose as a growth substrate (69); aspartase, which converts aspartate into both a carbon source and fumarate for respiration (27); and gamma-glutamyl transpeptidase, which converts glutathione into amino acids and glutamine into glutamate, each of which in turn can be used for growth (5,31). Chicken colonization defects were also observed in gluconate dehydrogenase (56) and hydrogenase (hydB) (81) mutant backgrounds, indicating the importance of gluconate and hydrogen gas, respectively, as electron donors in vivo.…”
mentioning
confidence: 99%
“…A number of recent studies have also demonstrated the importance of C. jejuni factors modulating metabolism and physiology during the colonization of animal hosts. These include nutrient utilization systems such as the cj0480c-cj0490 operon, allowing C. jejuni to use L-fucose as a growth substrate (69); aspartase, which converts aspartate into both a carbon source and fumarate for respiration (27); and gamma-glutamyl transpeptidase, which converts glutathione into amino acids and glutamine into glutamate, each of which in turn can be used for growth (5,31). Chicken colonization defects were also observed in gluconate dehydrogenase (56) and hydrogenase (hydB) (81) mutant backgrounds, indicating the importance of gluconate and hydrogen gas, respectively, as electron donors in vivo.…”
mentioning
confidence: 99%
“…Adherence and invasion of intestinal epithelial cells. The role of CsrA in adherence and invasion of host cells in vitro was determined as previously described (9,41,62). The csrA mutant exhibited a 5.4-fold decrease in the ability to adhere to INT407 cells (Fig.…”
mentioning
confidence: 99%
“…However, while both motility and adherence are certainly prerequisites for invasion, the adherence and invasion processes involve different proteins. For example, molecules that are involved uniquely in the invasion step but not in adherence include the Campylobacter invasion antigens, gamma-glutamyl transpeptidase, and the polysaccharide capsule (6,9,32). CsrA may therefore directly or indirectly regulate these or other invasion-specific Campylobacter proteins, and changes in the expression of these proteins may override any effect of the decrease in motility and result in the observed increase in invasion.…”
mentioning
confidence: 99%
“…cj1461 mutation causes hyperadherence to but decreased invasion of INT-407 cells. Adherence and invasion assays were conducted as previously described (2,25,34). Briefly, C. jejuni cells were centrifuged onto semiconfluent INT-407 cells at a multiplicity of infection of about 20, and the number of adherent bacteria was quantified after 3 h. Gentamicin (250 g/ml) was added to kill extracellular bacteria, and invasive bacteria were quantified after an additional 2 h incubation.…”
mentioning
confidence: 99%